2017
DOI: 10.1016/j.comppsych.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of post-hospitalization ecological momentary assessment in patients with psychotic-spectrum disorders

Abstract: Background Up to 50% of patients with psychotic-spectrum disorders are medication nonadherent. The use of real-time assessment via ecological momentary assessment (EMA) on mobile devices might offer important insights into adherence behaviors that cannot be measured in the clinic. However, existing EMA studies have only studied acutely ill patients during hospitalization or more stable patients in the community. Methods Feasibility and acceptability of EMA in 65 patients with psychotic-spectrum disorders who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
5
31
2
1
Order By: Relevance
“…In the “parent study” (Moitra et al, 2017), 49 patients returned the device at 1 month follow-up and 37 completed EMA surveys. In the current analysis, of the 37 who completed surveys, 12 participants were excluded due to completing too few surveys for use in time-lagged analysis (≤ 10 surveys).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the “parent study” (Moitra et al, 2017), 49 patients returned the device at 1 month follow-up and 37 completed EMA surveys. In the current analysis, of the 37 who completed surveys, 12 participants were excluded due to completing too few surveys for use in time-lagged analysis (≤ 10 surveys).…”
Section: Resultsmentioning
confidence: 99%
“…Details of study methods have been previously reported (Moitra et al, 2017). Eligibility criteria were: (a) currently hospitalized (inpatient/partial psychiatric hospital); (b) DSM-5 criteria for a schizophrenia-spectrum disorder or a mood disorder with psychotic features based on Structured Clinical Interview for DSM-IV (SCID); (c) 18 years or older; (d) prescribed oral antipsychotic medication; and (e) ability to speak/read English sufficiently to complete the assessments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several feasibility studies showed that mobile device delivered ESM assessments are well accepted even among patients with serious mental illness, with similar completion rates to those in other diseases (Edwards et al, 2016;Kimhy et al, 2006;Moitra et al, 2017).…”
Section: Implications For Clinical and Research Practicementioning
confidence: 99%
“…Misstrauen, paranoide Ideen, oder desorganisiertes Verhalten, sind häufige Symptome einer Psychose und stellen augenscheinlich zunächst ein Hindernis für eine EMA-Studie oder Intervention dar. Die aktuelle Studienlage zeigt jedoch, dass Personen mit Erkrankungen aus dem Psychosespektrum mit unterschiedlichen Symptomausprägungen erfolgreich eingeschlossen werden konnten, einschließlich Patienten mit akuten Halluzinationen, paranoiden oder anderen Wahnideen und formalen Denkstörungen (21,(24)(25)(26)(27)(28). Außerdem wurde EMA erfolg-reich in Studien durchgeführt, in denen Patienten mit simultanem Alkoholmissbrauch oder dem Konsum anderer Drogen eingeschlossen wurden (29)(30)(31)(32).…”
Section: Ema Bei Psychotischen Erkrankungenunclassified